Correlation among academic self-efficacy, professional identity, and professional attitude of higher vocational nursing students† - Xu Tian-Liang; Zhao Jiang-Nan; Zhang Yan-Yan; Jing Gai-Li (Sciendo, 2021)
To analyze the influence of professional identity and academic efficacy on the professional attitude of higher vocational nursing students.